2009
DOI: 10.1007/s00382-009-0629-1
|View full text |Cite
|
Sign up to set email alerts
|

A method for climate and vegetation reconstruction through the inversion of a dynamic vegetation model

Abstract: Climate reconstructions from data sensitive to past climates provide estimates of what these climates were like. Comparing these reconstructions with simulations from climate models allows to validate the models used for future climate prediction. It has been shown that for fossil pollen data, gaining estimates by inverting a vegetation model allows inclusion of past changes in carbon dioxide values. As a new generation of dynamic vegetation model is available we have developed an inversion method for one mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 38 publications
0
53
0
Order By: Relevance
“…been done for 30 sites in Europa and Garreta et al (2009) have shown that the mean bias was <1 • C and 3% in absolute value. Thus, the method seems to be unbiased.…”
Section: Application E: Dynamic Vegetation Modelmentioning
confidence: 96%
See 3 more Smart Citations
“…been done for 30 sites in Europa and Garreta et al (2009) have shown that the mean bias was <1 • C and 3% in absolute value. Thus, the method seems to be unbiased.…”
Section: Application E: Dynamic Vegetation Modelmentioning
confidence: 96%
“…Either PFT (Sitch et al, 2003) or species (Hickler et al, 2004) may be simulated. Garreta et al (2009) used the species version which includes 18 species. LPJ-GUESS has standard inputs, i.e.…”
Section: Vegetation Modellingmentioning
confidence: 99%
See 2 more Smart Citations
“…In this approach, several most likely climate scenarios are estimated for the time period in question, the vegetation model is run with each scenario and the simulated vegetation types are compared with the fossil pollen data to estimate the most coherent simulations. The past climate is obtained by inverting the climate input from the vegetation model (Guiot et al 1999(Guiot et al , 2009Garreta et al 2010). Wu et al (2007a) used an inverse modelling approach with modern and glacial CO 2 concentrations to investigate the impact of changing CO 2 concentration on the reconstruction results from Africa and Eurasia.…”
Section: Challenges and Future Developmentsmentioning
confidence: 99%